Biomass news - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
is a quarterly newsletter produced by the Biomass Users Network in Zimbabwe (BUN-Zimbabwe). Thepublication is a vehicle for indepth discussions of biomass: its appropriateness, its availability, its use and its potential forcorrecting environmental...